Profile of the Inclusive Education Program at Sedati Agung Sidoarjo Elementary School - Wilujeng Dwi Safitri; Vanda Rezania (Universitas Pendidikan Indonesia (UPI), 2023)
Inclusive education is an education program where children with special needs can participate in learning with normal children. This study aims to identify and describe the profile of the inclusive education program at SDN Sedati Agung Sidoarjo which includes teaching staff, curriculum, facilities and infrastructure and monitoring and evaluation in the school. This research is a descriptive qualitative research, with research subjects including school principals or inclusion coordinators, shadow teachers, and one special accompanying teacher. Data collection techniques used are observation, interview, and documentation methods. The research instruments used were observation guidelines and interviews. The analysis technique used is data reduction, data presentation, and drawing conclusions. To test the validity of the data, the credibility test and triangulation of techniques and sources and verification were used. The results of the study show that in Sedati Agung Elementary School the profile of the Inclusive Education Program; 1) teaching staff at Sedati Agung Elementary School, 2) the curriculum used is a non-fixed curriculum to suit the character of inclusive students and will be modified every 3 months to suit the potential of children with special needs taking into account their character (characteristics) and level of intelligence, 3) Facilities and facilities to serve children with special needs include special rooms, supporting tools and books to support services for children with special needs, 4) Monev is conducted to evaluate inclusive students through collaboration with parents to inform the progress of inclusive students.